DISPUTES OBSTETRIC ANESTHESIA - Enciso Nano, Jorge (2015)
I have taken the liberty of titling and the Obstetric Anesthesia because in reality there is currently no agreement this field to specify clearly that anesthetic technique should be used for certain Obstetric Pathology no uniformity of opinion as to the selection of the anesthetic technique used in these patients. While some argue that you should use certain scheme or technique, for this or that obstetric pathology, others refute this concept suggests other techniques, delimit other concepts there therefore a single criterion.